Moderation from Bias: A Field Experiment on Partisan Media in a New Democracy. - Conroy-Krutz, Jeffrey; Moehler, Devra C. (Journal of Politics, 2015)
Partisan media are often blamed for polarization in newly liberalized regimes. However, there is little empirical work on the subject, and information-processing theories suggest that extreme position taking is only one possible response to opinionated news. Rather, we theorize that partisan media may cause moderation in postliberalization settings, because low political sophistication and shifting political landscapes discourage partisan-motivated reasoning. We conducted a field experiment in Ghana in which tro-tros (commuter minibuses) were randomly assigned to one of four conditions. Passengers heard live talk-radio from a progovernment, pro-opposition, or neutral station, or were in a no-radio control. We find no effect of like-minded media on polarization, but significant evidence of moderation from crosscutting broadcasts, indicating that rival arguments persuaded subjects. Partisan broadcasts also encouraged displays of national over partisan identity. Rather than fueling extremism, we argue that partisan media can moderate by exposing citizens to alternate perspectives.